Pemanfaatan Database Kependudukan Untuk Daftar Pemilih Tetap Dengan Sistem Nota Kesepahaman dan Perjanjian Kerja Sama - Nurul Jannah Lailatul Fitria; Husni Mubaroq (Musamus Journal of Public Administration, 2021)
There is a classic problem in organizing general elections related to the voter list. The accuracy of the voter list reduces or minimizes errors in the implementation of general elections. The institution that plays an important role in organizing elections is the KPU and which controls the implementation of Bawaslu elections. One of the powers of the KPU is to compile a voter list. Meanwhile, Bawaslu supervises the general election implementation stage, including when the KPU compiles the voter list. Compiling the voter list requires data or materials related to the population database, the institution that has the authority for the population database is the Ministry of Home Affairs. Therefore, the author discusses the relationship between these institutions and the forms of cooperation carried out. The researcher uses a qualitative descriptive method by analyzing phenomena related to the object of research. So it can be seen that the Ministry of Home Affairs establishes a relationship with the KPU and Bawaslu with a Memorandum of Understanding and Cooperation Agreement System. The implementation of this activity is related to the use of the population database to determine the voter list in the implementation of general elections